2017
DOI: 10.1253/circj.cj-17-0108
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Suture vs. Ring Tricuspid Annuloplasty for Functional Tricuspid Regurgitation

Abstract: Background:Whether there is a significant difference in the long-term surgical outcomes between suture annuloplasty and ring annuloplasty for the treatment of functional tricuspid regurgitation (TR) is still controversial. We compared the long-term outcomes of tricuspid annuloplasty (TAP) with and without an annuloplasty ring. Methods and Results:From January 1996 to December 2015, we consecutively enrolled 684 patients (mean age, 65.5 years; 60% women) undergoing TAP for functional TR: 312 underwent conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The impact of age on TR progression was previously investigated. A study by Hata et al 17) revealed that older age was independent risk factor of recurrent moderate-to-severe TR. Kusajima et al 7) reported that age has an independent but minor impact on TR progression, with an OR of 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of age on TR progression was previously investigated. A study by Hata et al 17) revealed that older age was independent risk factor of recurrent moderate-to-severe TR. Kusajima et al 7) reported that age has an independent but minor impact on TR progression, with an OR of 1.1.…”
Section: Discussionmentioning
confidence: 99%
“…De Vega suture annuloplasty has been abandoned most Institutions and in many reports provides worse results than other device 37‐40 . However, some studies showed similar results between De Vega suture annuloplasty and ring 32,33,41 . Nevertheless, in our experience De Vega suture annuloplasty, technically, has not lower freedom from TR return than use of bands or rings.…”
Section: Discussionmentioning
confidence: 49%
“…Whether the surgical technique could influence TR recurrence remains debated 30‐33 . In our experience, no difference was observed according to the surgical strategy.…”
Section: Discussionmentioning
confidence: 57%
“…Whether the surgical technique used for TAP could affect surgical results remains a matter of debate . Many studies support the use of rigid, or flexible devices, or report similar results with suture annuloplasty vs flexible or rigid devices, or with flexible vs rigid devices .…”
Section: Discussionmentioning
confidence: 99%